Mitochondrial membrane protein-associated neurodegeneration: a case report and literature review - Dušek, Pavel; Školoudík, David; Roth, Jan; Dušek, Petr (Neurocase, 2018)
Mitochondrial membrane protein-associated neurodegeneration (MPAN) is an autosomal recessive disorder caused by mutation in the C19orf12 gene. We report a compound heterozygous c.[32C>T];[205G>A;424A>G] (p.[Thr11Met];[Gly69Arg;Lys142Glu]) Czech patient who manifested with right foot dystonia, impaired handwriting, attention deficit, and signs of iron accumulation on brain MRI. Gradually, he developed dysarthria, spastic-dystonic gait, pedes cavi, and atrophy of leg muscles. Additionally, we report demographic parameters, clinical signs, and allelic frequencies of C19orf12 mutations of all published MPAN cases. We compared the most frequent mutations, p.Thr11Met and p.Gly69ArgfsX10; the latter was associated with younger age at onset and more frequent optic atrophy in homozygotes.
Keywords: iron accumulation; transportní proteiny mitochondriální membrány; neuroaxonální dystrofie; Humans; Iron Metabolism Disorders; mladý dospělý; dospělí; parkinsonism; lidé; MPAN; poruchy metabolismu železa; Adult; Neuroaxonal Dystrophies; Male; interleukiny; Young Adult; Interleukins; Mitochondrial Membrane Transport Proteins; neurodegeneration; mužské pohlaví; C19orf12 mutation